Time Transfer in a 1839-km Telecommunication Fiber Link Demonstrating a Picosecond-Scale Stability - Guo, Xinxing; Hou, Bing’an; Liu, Bo; Yang, Fan; Kong, Weicheng; Liu, Tao; Dong, Ruifang; Zhang, Shougang (Chinese physics letters, 2024)
An implementation of high-precision time transfer over a 1839-km field fiber loop back link between two provincial capitals of China, Xi’an and Taiyuan, is reported. Time transfer stabilities of 6.5 ps at averaging time of 1 s and 4.6 ps at 40000 s were achieved. The uncertainty for the time transfer system was evaluated, showing a budget of 56.2 ps. These results stand for a significant milestone in achieving high-precision time transfer over a field fiber link spanning thousands of kilometers, signifying a record-breaking achievement for the real-field time transfer in both stability and distance, which paves the way for constructing the nationwide high-precision time service via fiber network.